Green Marketing, Online Customer Reviews, and Impulse Buying: The Mediating Role of Perceived Seller Digital Competence - Aris Indriyanti; Hening Nakuloadi; Supriyono Supriyono; Oryza Ruly Adhiyani; Ratna Ambar Mintarsih; Muh Adzam (CV. Sakura Digital Nusantara, 2026)
Purpose –The rapid development of marketplace platforms has increased consumers’ exposure to environmental marketing claims and customer-generated product information, both of which may trigger unplanned purchasing decisions. This study examines the effects of green marketing and online customer reviews on impulse buying, with perceived seller digital competence as a mediating variable among marketplace consumers. Methodology - This study employed a quantitative cross-sectional survey involving 200 Indonesian marketplace consumers who had made at least one unplanned purchase, encountered green marketing content, and read online customer reviews before purchasing. Respondents were selected using purposive sampling. Data were collected through a five-point Likert-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling. Finding - Green marketing and online customer reviews have positive and significant effects on impulse buying. Perceived seller digital competence also positively affects impulse buying and mediates the effects of green marketing and online customer reviews. These findings indicate that consumers are more likely to make spontaneous purchases when sellers are perceived as capable of communicating product information clearly, managing customer reviews professionally, and using marketplace features effectively. Originality - This study extends the Stimulus–Organism–Response framework by conceptualizing perceived seller digital competence as a consumer-level cognitive appraisal that links digital marketing stimuli with impulse buying. Unlike actual employee competence, this construct represents consumers’ evaluations of sellers’ digital communication and service capabilities.